Block modulus precoding for blind multiuser detection of DS-CDMA signals. - Al-Bayati, A.K.S (IEEE Transactions on communications)
We propose a blind multiuser detector based on a new data precoding technique for direct-sequence code-division multiple-access signals. The modulus of all users' data is block encoded, using a sequence that is unique for each user. This precoding method, together with the analytical constant modulus algorithm for detection, enables a closed-form, one-shot detection of the desired user's signal in a multipath channel using one or more antennas. The detection process does not involve or require a channel estimation step. The proposed detector is shown to be extremely near-far resistant, and can operate properly in the presence of severe carrier frequency offset.